THE IMPACT OF THE GENERAL BUDGET ON THE EXCHANGE RATE IN IRAQ - Lect. Dr. Jabbar Saadoon Darag (American Journals Publishing, 2024)
The study included the concept of the general budget and the factors affecting it, as well as the concept of the exchange rate and the factors affecting it. Data were used, through the Central Bank of Iraq for the period 2004-2023, and the results of the study were that there was a significant relationship between the two variables in the short term and the long term, through the integration program. Joint and Single Test – Equation cointegration.
Keywords: Exchange rate, general budget, and Single-Equation cointegration test